2016
DOI: 10.1002/2016jb012967
|View full text |Cite
|
Sign up to set email alerts
|

Role of critical state framework in understanding geomechanical behavior of methane hydrate‐bearing sediments

Abstract: A proper understanding of geomechanical behavior of methane hydrate‐bearing sediments is crucial for sustainable future gas production. There are a number of triaxial experiments conducted over synthetic and natural methane hydrate (MH)‐bearing sediments, and several soil constitutive models have been proposed to describe their behavior. However, the generality of a sophisticated model is questioned if it is tested only for a limited number of cases. Furthermore, it is difficult to experimentally determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 47 publications
(90 reference statements)
1
35
0
Order By: Relevance
“…The set of critical state parameters characterizing the behavior of pure Toyoura sand (ie, hydrate‐free sediment) (Table ) has been calibrated here using the stress‐strain curve and the volumetric response of the host specimen used for the synthetic formation of cementing hydrate ( S h = 0% in Figure C). For the calibration process, values adopted in previous publications that also model the mechanical response of Toyoura sand have been used as a reference . In addition, the different void ratios of 0.6 and 0.75 reported for the cementing and pore‐filling specimens, respectively, have also been considered in the simulations (Table ).…”
Section: Hydrate‐casm Performancementioning
confidence: 99%
See 3 more Smart Citations
“…The set of critical state parameters characterizing the behavior of pure Toyoura sand (ie, hydrate‐free sediment) (Table ) has been calibrated here using the stress‐strain curve and the volumetric response of the host specimen used for the synthetic formation of cementing hydrate ( S h = 0% in Figure C). For the calibration process, values adopted in previous publications that also model the mechanical response of Toyoura sand have been used as a reference . In addition, the different void ratios of 0.6 and 0.75 reported for the cementing and pore‐filling specimens, respectively, have also been considered in the simulations (Table ).…”
Section: Hydrate‐casm Performancementioning
confidence: 99%
“…The results presented in this section have been validated against the outputs from three other mechanical models for MHBS (Figure ). The comparison is satisfactory and shows that despite the simplicity of the densification mechanism, the Hydrate‐CASM performs similarly to models that require more than one hydrate‐related empirical parameter in their formulation.…”
Section: Hydrate‐casm Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The soil material within each core sample was assumed to be a homogenized continuum with isotropic mechanical properties. Uchida et al (2016) demonstrated that the MHCS model is sufficient to capture the geomechanical behavior of the hydrate-bearing sediments tested at various institutes under different confining stresses and with varying degrees of hydrate saturation. Therefore, the MHCS model was used to simulate the triaxial tests and match the mechanical response curves with the laboratory triaxial test results.…”
Section: Sand and Clay Isotropic Model Parametersmentioning
confidence: 99%